Faktor-Faktor Yang Mempengaruhi Profitabilitas Perusahaan (Jurnal Paradigma Akuntansi, 2022)
The purpose of this study is to determine the effect of total assets turnover, current ratio, debt to assets ratio, and firm size on profit growth of 2)manufacturing companies listed on the Indonesian stock exchange in the period of 2017-2019. 3) This study uses purposive sampling method with 4) total sample of 185 data. 5)data processing techniques using 6) multiple regression analysis assisted by SPSS (Statistical Product and Service Solution) program for Windows released 25 and Microsoft Excel 2013. 7 The results of this study indicate that total assets turnover has no significant effect on profit growth, current ratio has no significant effect on profit growth, debt to assets ratio has no significant effect on profit growth, and firm size has no significant effect on profit growth. 8) The implication of this research is that total assets turnover, current ratio, debt to assets ratio, firm size, profit growth are not things that need to be considered in order to determine profit growth because some of these factors do not have a significant effect on profit growth.